METHODOLOGY OF PREPARING STUDENTS FOR SCIENTIFIC RESEARCH WITH THE HELP OF LABORATORY TRAINING ON THE TOPIC “GEARS” - Nurova, Oliya Salomovna (Educational Research in Universal Sciences, 2022)
The need to prepare students for scientific-research activity is based on the most important component of the qualification characteristics of a future engineer. The analysis of scientific, scientific-methodical, psychological and pedagogical literature made it possible to determine the research ability. By means of research abilities, abilities that ensure that students acquire scientific knowledge methods in the course of educational activities, and shape the interest and need of a person in creative (research) activities are meant.